2021
DOI: 10.3897/herpetozoa.34.e58496
|View full text |Cite
|
Sign up to set email alerts
|

Demography and spatial activity of fire salamanders, Salamandra salamandra (Linnaeus, 1758), in two contrasting habitats in the Vienna Woods

Abstract: Understanding population dynamics is vital in amphibian conservation. To compare demography and movements, we conducted a capture-recapture study over three spring seasons in two populations of Salamandra salamandra in the Vienna Woods. The study sites differ in topography, vegetation, and the type of breeding waters. Population density in a beech forest traversed by a stream was more than twice as high as in an oak-hornbeam forest with temporary pools. Movement distances were on average higher at the latter s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The median movement distances and home range sizes we observed were considerably larger than those reported for urban populations of S. salamandra inhabiting similar-sized forest patches next to permanent streams (e.g. Vienna; Burgstaller et al, 2021). Therefore, differences in movement distances cannot be attributed to differences in area or habitat.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The median movement distances and home range sizes we observed were considerably larger than those reported for urban populations of S. salamandra inhabiting similar-sized forest patches next to permanent streams (e.g. Vienna; Burgstaller et al, 2021). Therefore, differences in movement distances cannot be attributed to differences in area or habitat.…”
Section: Discussioncontrasting
confidence: 73%
“…Movement patterns have not been observed to differ between sexes in other S. salamandra populations in central Europe (e.g. Burgstaller et al, 2021). However, Manenti et al (2017) found that male S. salamandra were more active in microhabitats close to breeding sites, where they might have a higher chance of mating with females.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations